Latinx fathers report low awareness and knowledge of the human papillomavirus vaccine, but high willingness to vaccinate their children if recommended by a healthcare provider: A qualitative study. Issue 11 (2nd November 2022) - Lindsay, Ana Cristina; Delgado, Denisse; Valdez, Madelyne J.; Granberry, Phillip
ABSTRACT: This descriptive qualitative study explored Latinx fathers' awareness, knowledge, and acceptability of the human papillomavirus (HPV) vaccine for their adolescent children. Data were collected through individual, semi-structured interviews and analysed using a hybrid method of thematic analysis that incorporated deductive and inductive approaches. Nineteen, majority foreign-born Latinx fathers participated. Four main themes and two subthemes emerged from the analyses. Results found fathers' low awareness and knowledge of HPV and the HPV vaccine. Results also identified fathers' positive attitudes toward vaccines in general. Moreover, results revealed fathers trust in healthcare providers and high willingness to vaccinate their children against HPV if recommended by their child's primary healthcare provider. Findings indicate the need for increased efforts to raise awareness and knowledge among Latinx fathers of HPV and the HPV vaccine. Given the limited research focused on Latinx fathers, the study's findings are valuable in building a knowledge foundation for developing future studies and interventions to promote the HPV vaccine targeting Latinx fathers living in the United States. Future research should quantify Latinx fathers' awareness, knowledge, and acceptability of the HPV vaccine for their sons and daughters and assess fathers' role in the decision-making process to vaccinate their children against HPV.